A simulation study on the necessity of working breakdown in a state dependent bulk arrival queue with disaster and optional re-service. (13th July 2022) - Merit, C.K. Deena; Haridass, M.
Sudden increase in service requests immediately after an occurrence of a disaster due to the scarcity of resources creates congestion in service. Effective queue management should ensure that the services are available for every request with an acceptable delay. Unexpected breakdowns causing huge delays were observed many times in real-life scenarios. The working breakdown is introduced in this paper to address this issue in an M X / G /1 disaster queueing system wherein an occurrence of a disaster at the main server is handled immediately by replacing a substitute server with a different or same service rate. State-dependent arrival and optional re-service are also included to make this model more robust. Various performance indices were established using the supplementary variable technique. Numerical illustration and simulation was done for validation and verification respectively. It has been proved that the working breakdown is effective when the arrival rate is tremendously larger immediately after a disaster.